Investigating the Relationship of Inflammatory Cytokines and Brain-Derived Neurotrophic Factor with Cognitive Functions in Multiple Sclerosis Patients - Narges َArab-Moghaddam; Karim Asgari Mobarakeh; Gholamreza Daryabor; Maryam Poursadeghfard (پژوهش‌های کاربردی روانشناختی)
The aim of this study was to investigate the relationship between immunological factors and cognitive functions in patients with multiple sclerosis (MS). The methodology was fundamental in nature, and the research design was correlational. Patients diagnosed with multiple sclerosis comprised the research population. 68 patients with multiple sclerosis (MS) were selected through convenience sampling. These patients were divided into three groups: 23 newly diagnosed patients (ND), 23 patients with relapsing-remitting MS (RRMS), and 22 patients with secondary progressive types (SPMS). The patients were 55 women and 13 men. Additionally, the control group consisted of 22 healthy individuals (17 women and 5 men) who were matched based on their age, gender, and educational background. The ELISA method was used to measure the serum levels of cytokines IFN-γ, IL-6, TNF-α, and IL-17, as well as brain-derived neurogenesis factor (BDNF) in the control group and the patients. California Verbal Learning Tests (CVLT-11), Brief Spatial Memory-Revised (BVMT-R), Symbol Digit Substitution (SDMT), Verbal Fluency (COWAT), and Executive Functions (D-KEFS) were implemented to assess cognitive functions. SPSS-26 software was employed to analyze the data that was obtained using the regression method. Compared to the control group, patients exhibited substantial variations in cognitive functions and serum levels of cytokines IFN-γ, IL-17, and BDNF. In RRMS and ND patients, BDNF was a positive predictor of visual-spatial memory and executive function. In ND patients, IFN-γ was a negative predictor of executive function, and TNF-α was a negative predictor of information processing speed in SPMS patients. Neurotrophic factor BDNF and cytokines IFN-γ and IL-17 are potential biomarkers for the assessment of certain cognitive functions in patients with multiple sclerosis.